2012
DOI: 10.1016/j.jmoldx.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of the LightCycler MRSA Advanced Test, the Xpert MRSA Assay, and MRSASelect Directly Plated Culture with Simulated Workflow Comparison for the Detection of Methicillin-Resistant Staphylococcus aureus in Nasal Swabs

Abstract: Rapid detection of nasal colonization with methicillin-resistant Staphylococcus aureus (MRSA) followed by appropriate infection control procedures reduces MRSA infection and transmission. We compared the performance and workflow of two Food and Drug Administration-approved nucleic acid amplification assays, the LightCycler MRSA Advanced Test and the Xpert MRSA test, with those of directly plated culture (MRSASelect) using 1202 nasal swabs collected at three U.S. sites. The sensitivity of the LightCycler test (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
(33 reference statements)
0
6
1
Order By: Relevance
“…LightCycler® MRSA Advanced Test was more sensitive for the detection of MRSA (84.38%) than Detect-Ready® MRSA Kit, but both tests had poorer sensitivities in our real-life study setting than reported in previous studies [36]. Especially the Detect-Ready® MRSA Kit had a surprisingly low clinical sensitivity (57.69%).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…LightCycler® MRSA Advanced Test was more sensitive for the detection of MRSA (84.38%) than Detect-Ready® MRSA Kit, but both tests had poorer sensitivities in our real-life study setting than reported in previous studies [36]. Especially the Detect-Ready® MRSA Kit had a surprisingly low clinical sensitivity (57.69%).…”
Section: Discussioncontrasting
confidence: 57%
“…More expensive molecular-based test systems show more interesting turn-over-times but only few studies estimating accuracy values in a routine diagnostic setting are available so far [36]. Data of the Detect-Ready® MRSA Kit concerning these questions are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…If positive, the specimen is assigned positive screen status. [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] This methodology (called "partial verification") introduces bias in favor of PCR. 115 For MRSA, Yam et al 99 tested 1,246 nares swab specimens with the Lightcycler MRSA Advanced (Roche Molecular Diagnostics, Basel Switzerland), a laboratory developed test (LDT) PCR and, in parallel, cultured all specimens.…”
Section: Shedding Timementioning
confidence: 99%
“…Roche Diagnostics has developed a LightCycler MRSA Advanced Test system for RT-PCR detection of MRSA directly from nasal swabs with overall 83.3% sensitivity and 99% specificity [ 64 ]. It was found that the sensitivity and specificity are similar between the LightCycler MRSA Advanced Teat and the Xpert MRSA assay for detection of MRSA from human swab specimens [ 65 ].…”
Section: Identification Of Mrsa Using Different Automated Mrsa Rt-pcrmentioning
confidence: 99%